Development, Validation, and Diagnostic Accuracy of the Fetal Lack of Responsiveness Scale for Diagnosis of Severe Perinatal Hypoxia - Luis Carlos Franco; Sandra M. Buitrago; Isabel Arbelaez; Laura F. Pinto; Daniela Blanco; María C. Pizarro; Laura Santamaria; Catalina Trillos (Journal of Pregnancy)
Conclusions: FLORS demonstrated significant internal consistency and observer agreement, with a promising sensitivity–specificity balance and significant AUC. Further research is needed to assess its impact on perinatal hypoxia and cesarean delivery.